2013
DOI: 10.7314/apjcp.2013.14.10.5579
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells in Head and Neck Squamous Cell Carcinoma: A Review

Abstract: Research indicates that a small population of cancer cells is highly tumorigenic, endowed with the capacity for self-renewal, and has the ability to differentiate into cells that constitute the bulk of tumors. These cells are considered the ''drivers'' of the tumorigenic process in some tumor types, and have been named cancer stem cells (CSC). Epithelial-mesenchymal transition (EMT) appears to be involved in the process leading to the acquisition of stemness by epithelial tumor cells. Through this process, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 83 publications
1
44
0
6
Order By: Relevance
“…CD44, a specific receptor for hyaluronic acid and adhesion/homing molecule (Naor et al, 2008;Jaggupilli and Elkord, 2012), is a multifunctional class I transmembrane glycoprotein expressed in almost all normal and cancer cells (Naor et al, 2008;Jaggupilli and Elkord, 2012). In several previous studies, CD44 individually or in combination with other putative CSC markers has been applied to isolate CSCs in various solid tumors including breast (Al-Hajj et al, 2003), prostate, pancreas (Immervoll et al, 2011), ovarian, colorectal (Wielenga et al, 1993;Woodman et al, 1996;Choi et al, 2009), head and neck (Satpute et al, 2013) and bladder cancers (Yang and Chang, 2008;Chan et al, 2009;Slomiany et al, 2009;Lee et al, 2010;Su et al, 2010;Jaggupilli and Elkord, 2012). Both in vitro and in vivo studies have shown that CD44+ bladder cancer cells have higher tumorigenic potential compared to CD44-bladder cancer cells; whereas they have lower tumorigenic potential compared to ALDH1A1+ cells .…”
Section: Introductionmentioning
confidence: 99%
“…CD44, a specific receptor for hyaluronic acid and adhesion/homing molecule (Naor et al, 2008;Jaggupilli and Elkord, 2012), is a multifunctional class I transmembrane glycoprotein expressed in almost all normal and cancer cells (Naor et al, 2008;Jaggupilli and Elkord, 2012). In several previous studies, CD44 individually or in combination with other putative CSC markers has been applied to isolate CSCs in various solid tumors including breast (Al-Hajj et al, 2003), prostate, pancreas (Immervoll et al, 2011), ovarian, colorectal (Wielenga et al, 1993;Woodman et al, 1996;Choi et al, 2009), head and neck (Satpute et al, 2013) and bladder cancers (Yang and Chang, 2008;Chan et al, 2009;Slomiany et al, 2009;Lee et al, 2010;Su et al, 2010;Jaggupilli and Elkord, 2012). Both in vitro and in vivo studies have shown that CD44+ bladder cancer cells have higher tumorigenic potential compared to CD44-bladder cancer cells; whereas they have lower tumorigenic potential compared to ALDH1A1+ cells .…”
Section: Introductionmentioning
confidence: 99%
“…They are similar to stem cells and are capable of both self-renewal and differentiation into all of the cells within a tumor (Siclari and Qin, 2010;Rangwala et al, 2011). CSCs have been identified in a number of cancers including acute myeloid leukaemia (AML) (Bonnet and Dick, 1997;Passegue et al, 2003), glioblastoma (Singh et al, 2003), breast (Al-Hajj et al, 2003;Ponti et al, 2005), lung (Kim et al, 2005), prostate (Collins et al, 2005), ovarian (Bapat et al, 2005), gastric (Houghton et al, 2004), esophagous ( Li et al, 2013 ), Head and Neck SCC (Satpute et al, 2013) and skin cancers (Frank et al, 2005;Monzani et al, 2007). Different markers have been identified to be expressed on melanoma stem cells (Quintana et al, 2010;Shakhova and Sommer, 2013) comprising CD20 (Fang et al, 2005) and ABC transporter family members such as MDR1, ABCG2 and ABCB5 (Frank et al, 2003;Frank et al, 2005;Monzani et al, 2007;Keshet et al, 2008;Schatton et al, 2008), CD271 (Boiko et al, 2010;Civenni et al, 2011), CD44 (Fernandez-Figueras et al, 1996, CD133 (Klein et al, 2006) and Nestin (Piras et al, 2010;Fusi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, rational that human myeloblastic leukemia derives from stem cells [6]. TICs with CD133 + expression have been subsequently identified in various solid tumors, such as breast cancer, brain tumour, prostate cancer, malignant melanoma, colon cancer, liver cancer, pancreatic cancer and head and neck squamous cell carcinoma, though CD133 + cancerous cells have not been classified as cancer stem cells of stomach until now [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%